Analisis Kinerja Jalan pada Ruas Jalan Jemur Andayani, Kecamatan Wonocolo, Kota Surabaya, Jawa Timur - Afifah Nor Fadhilah; Siti Nuurlaily Rukmana; Yuni Lestari; Virli Delia Monika; Farid Pranowo; Rifan Pramudya; Aldin (Seminar Nasional Hasil Riset dan Pengabdian, 2024)
Jemur Andayani Street is a secondary arterial road facing traffic issues during peak hours such as morning, noon, and late afternoon. This is due to diverse land use including offices, educational institutions, commercial enterprises, industries, and residential areas. Key challenges identified include traffic entering and exiting from offices, improper parking, and vehicles stopping abruptly, disrupting road performance due to high traffic volumes and often causing congestion at certain times. The study aims to address congestion issues by enhancing existing infrastructure performance through optimization. Data collection methods employed include observation of road geometric conditions, traffic flow, side obstacles, documentation, literature review, and data analysis to support development planning. Survey results indicate peak traffic flows in the evening westbound and morning eastbound on Jemur Andayani Street during weekdays. Based on these findings, plans are underway to develop public transportation facilities and infrastructure by adding and maintaining facilities, and improving public transportation services to reduce private vehicle usage. Other measures include providing pedestrian crossings, dedicated bike lanes, and controlling vehicle parking to maximize road utilization. Keywords: Traffic study, traffic congestion, urban transportation Abstrak Jalan Jemur Andayani is a secondary arterial road facing traffic issues during peak hours such as mornings, afternoons, and evenings. This is due to varied land uses including offices, educational institutions, commercial activities, industries, and residential areas. The main constraints identified include vehicle movements to and from offices, indiscriminate parking, and sudden stops or pulls-over that disrupt road performance due to high traffic volumes, often causing congestion at certain times. This study aims to address congestion issues by enhancing infrastructure performance through optimization. It combines qualitative and quantitative descriptive research methods. Data collection involved direct surveys for primary data and literature reviews for secondary data. Survey results indicate peak traffic flow in the afternoon westbound and morning eastbound on Jalan Jemur Andayani during weekdays. Based on these findings, recommendations include the development and maintenance of public transport facilities, provision of zebra crossings, dedicated bicycle lanes, and parking spaces. Kata Kunci : Studi lalu lintas , kemacetan lalu lintas, transportasi perkotaan